Higher incidence of chemotherapy induced oral mucositis in females: a supplement of multivariate analysis to a randomized multicentre study - Vokurka, Samuel; Bystrická, Eva; Koza, Vladimír; Scudlová, Jana; Pavlicová, Vladislava; Valentová, Dana; Visokaiová, Maria; Misaniová, Lubica (Supportive care in cancer, 2006)
Study on the normal saline vs povidone-iodine mouthwashes for oral mucositis (OM) prophylaxis in patients after high-dose chemotherapy comprising bischloroethyl nitrosourea etoposide ara-C melphalan (BEAM) or high-dose melphalan (HD-L-PAM) followed by autologous peripheral stem cell transplantation indicated that females have higher a incidence of OM compared to men, as reported by [Vokurka et al. 13:554-558, (2005)]. The multivariable analysis of larger cohort of 148 patients compliant with the original study protocol confirmed female gender to be an independent risk factor and predictor for OM. The HD-L-PAM (200 mg/m2) conditioning regimen revealed to be more toxic compared to BEAM as for incidence of OM grades 3-4 World Health Organization score. Body mass index, age, mouthwash solution used, and CD34+ cell number in the autologous graft were verified not to have an impact on OM incidence in this group of patients.
Keywords: Predictive Value of Tests; Multivariate Analysis; stomatitida; Adolescent; cytarabin; Adult; senioři; incidence; Aged; Male; lidé; Analysis of Variance; Transplantation, Autologous; lidé středního věku; Humans; Randomized Controlled Trials as Topic; etoposid; sexuální faktory; randomizované kontrolované studie jako téma; stupeň závažnosti nemoci; Antineoplastic Combined Chemotherapy Protocols; Incidence; Multicenter Studies as Topic; Middle Aged; Sex Factors; Etoposide; prediktivní hodnota testů; vředy v ústech; melfalan; multicentrické studie jako téma; autologní transplantace; Peripheral Blood Stem Cell Transplantation; protokoly protinádorové kombinované chemoterapie; Cytarabine; Oral Ulcer; rizikové faktory; mužské pohlaví; analýza rozptylu; dospělí; karmustin; Stomatitis; ženské pohlaví; mladiství; transplantace periferních kmenových buněk; Severity of Illness Index; Female; Carmustine; Risk Factors; Melphalan; multivariační analýza